Reengineering of Health Vocational Programs in SMK/MAK: Integration of Islamic Education, Implementation of Health Law No. 17 of 2023, and Reflections from Thailand's Vocational Education Reform 4.0 - Kautsar Eka Wardhana; Muhammad Solekhin; Muhammad Saparuddin; Dewi Kusuma; Maso Sareh (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study explores the reengineering of health vocational high school (SMK Kesehatan) curricula in Kalimantan following the implementation of Indonesia’s Health Law No. 17 of 2023, with a comparative analysis of Thailand’s vocational education reform under the Thailand 4.0 framework. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation in SMKs located in East, South, and Central Kalimantan. Findings reveal that SMKs in Kalimantan have begun to adjust their curricula by emphasizing medical technology, hospital management, and digital health information systems. However, challenges such as limited facilities, insufficient teacher training, and weak industry partnerships remain significant barriers. In contrast, Thailand has successfully implemented holistic vocational education reform by integrating work-integrated learning, providing high-skilled vocational innovation scholarships, and establishing strong partnerships between schools and industries. Thailand’s model also benefits from a robust monitoring and evaluation system that ensures alignment with labor market demands. These findings suggest that SMKs in Kalimantan need to adopt a more holistic and collaborative approach to curriculum reengineering, drawing lessons from Thailand, to produce graduates who are adaptive, innovative, and competitive in the global health sector.